An Intramolecular Hydrogen‐Shift in a Peroxy Radical at Cryogenic Temperatures: The Reaction of 2‐Hydroxyphenyl Radical with O2. Issue 53 (4th September 2020) - Wagner, J. Philipp
Abstract: Peroxy radical hydrogen‐shifts are pivotal elementary reaction steps in the oxidation of small hydrocarbons in autoignition and the lower atmosphere. Although these reactions are typically associated with a substantial barrier, we demonstrate that the [1, 5]H‐shift in the peroxy species derived from the 2‐hydroxyphenyl radical 1 is so facile that it even proceeds rapidly in an argon matrix at 35 K through a proton‐coupled electron transfer mechanism. Hydrogen‐bound complexes of o ‐benzoquinone are identified as the main reaction products by infrared spectroscopy although their formation through O−O bond scission is hampered by a barrier of 11.9 kcal mol −1 at the ROCCSD(T)/cc‐pVTZ/UB3LYP/6–311G(d, p) level of theory. Abstract : Addition of O2 to the 2‐hydroxyphenyl radical at cryogenic temperatures does not stop at the peroxy radical, but leads to a facile hydrogen‐shift through a proton‐coupled electron transfer mechanism and O−O bond breaking instead.